Produção silvícola no montado.: Análise e reflexão sobre a gestão sustentada dos montados de sobreiro - Ferreira, A. G.; Ribeiro, N. A. (Revista de Ciências Agrarias, 2007)
“Montados” are systems where several productions are in dynamic equilibrium both in space and time. This spatial and temporal organisation enabled the system maintenance by the hazard control of each production, which is related with the climatic variability of the Mediterranean climate. The “montados” are characteristic of the south of Portugal, where the cork oak is the mostly frequent. In the cork oak “montados” the main production is cork, mostly associated with grazing and/or agriculture. It should also be stated the important role of the “montado” in the soil and water conservation, habitat and biodiversity conservation and amenities. The maintenance of the “montado” productive potential is associated to their resilience, which is especially dependent on the soil. The identification system fragilities allow pointing out guide lines for the sustainable management of the cork oak “montados”.
Keywords: água; gestão sustentada; montado; regeneração (voyant); solo